Validation of the Unesp-Botucatu composite scale to assess acute postoperative abdominal pain in sheep (USAPS) - Silva, Nuno Emanuel Oliveira Figueiredo [UNESP]; Trindade, Pedro Henrique Esteves [UNESP]; Oliveira, Alice Rodrigues [UNESP]; Taffarel, Marilda Onghero; Moreira, Maria Alice Pires; Denadai, Renan [UNESP]; Rocha, Paula Barreto [UNESP]; Luna, Stelio Pacca Loureiro [UNESP] (Public Library of Science (PLoS), 2020)
A scale with robust statistical validation is essential to diagnose pain and improve decision making for analgesia. This blind, randomised, prospective and opportunist study aimed to develop an ethogram to evaluate behaviour and validate a scale to assess acute ovine postoperative pain. Elective laparoscopy was performed in 48 healthy sheep, filmed at one preoperative and three postoperative moments, before and after rescue analgesia and 24 hours after. The videos were randomised and assessed twice by four evaluators, with a one-month interval between evaluations. Statistical analysis was performed using R software and differences were considered significant when p <0.05. Based on the multiple association, a unidimensional scale was adopted. The intra- and inter-observer reliability ranged from moderate to very good (intraclass correlation coefficient ≥ 0.53). The scale presented Spearman correlations > 0.80 with the numerical, simple descriptive, and visual analogue scales, and a correlation of 0.48 with the facial expression scale. According to the mixed linear model, the scale was responsive, due to the increase and decrease in pain scores of all items after surgery and analgesic intervention, respectively. All items on the scale demonstrated an acceptable Spearman item-total correlation (0.56-0.76), except for appetite (0.25). The internal consistency was excellent (Cronbach's α = 0.81) and all items presented specificity > 0.72 and sensitivity between 0.61-0.90, except for appetite. According to the Youden index, the cut-off point was ≥ 4 out of 12, with a diagnostic uncertainty zone of 4 to 5. The area under the curve > 0.95 demonstrated the excellent discriminatory capacity of the instrument. In conclusion, the Unesp-Botucatu pain scale in sheep submitted to laparoscopy is valid, reliable, specific, sensitive, with excellent internal consistency, accuracy, discriminatory capacity, and a defined cut-off point.